Four new species of Tipula (Sinotipula) Alexander (Diptera, Tipulidae) from China and a new replacement name in Tipula (Vestiplex) Bezzi, 1924 - Yang, Qi-cheng; Ren, Jin-long; Liu, Xiao-yan; Yang, Ding (European Journal of Taxonomy, 2023)
Fourteen species of the subgenus Sinotipula (Diptera, Tipulidae) were previously known to occur in China. Here four species are described and illustrated as new to science: Tipula (Sinotipula) drolma sp. nov., T. (S.) forcipicauda sp. nov., T. (S.) heminga sp. nov. and T. (S.) longiloba sp. nov. The following three species are redescribed: T. (S.) exquisita Alexander, 1935, T. (S.) hobsoni Edwards, 1928 and T. (S.) wardi Edwards, 1928, and a key to the species of Tipula (Sinotipula) from China is presented. We also give a new replacement name for Tipula (Vestiplex) bucera Yang, Li, Pan, Liu & Yang, 2021, i.e., T. (V.) curvicornis nom. nov.